Online Learning Solution: Ice Breaking Application to Increase Student Motivation - Hendrik Pratama; Tri Wahyuni Maduretno; Andista Candra Yusro (Universitas Negeri Makassar, 2021)
The purpose of this study was to find out the effectiveness of ice breaking as an effort to increase the students’ learning motivation. This research was conducted in the Science Education Study Program of STKIP PGRI Nganjuk, East Java, Indonesia. The sample in this study was 25 students in the third semester who took the mechanics course.The sample used in this study was taken using purposive sampling technique. This type of comparative research is used in this study. Data collection techniques used, questionnaires, observation sheets, and documentation. This type of research is comparative which is used to examine differences in student learning motivation before and after being treated. The results of the study were based on the Paired T Test shows value probability/ p Paired T test value of 0.000. This means that there are differences in student learning motivation after being given the ice breaking learning model. This ice breaking was implemented as an effort to reduce saturation and boredom of the students during the learning process. The new thing that is obtained is that the application of games can increase learning motivation